2022
DOI: 10.3390/agronomy12040922
|View full text |Cite
|
Sign up to set email alerts
|

Best Linear Unbiased Predictions of Environmental Effects on Grain Yield in Maize Variety Trials of Different Maturity Groups

Abstract: Development of new cultivars and agronomic improvements are key factors of increasing in future grain yield in maize grown in environments affected by climate change. Assessment of value for cultivation and use (VCU) reflects the results of latest breeding efforts showing yield trends, whereby external environmental covariates were rarely used. This study aimed to analyze several environmental effects including stress degree days (SDD) on grain yields in Croatian VCU trials in three maturity groups using linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Such results indicate that the location affects the non-additive gene actions more than additive genetic effects in tasseling. However, Aly and Mousa (2011) and Zoric et al (2022) have reported significant GCA and SCA variances for most characters including tasseling in maize, emphasizing the function of both additive and non-additive components. GCA variances for tasseling were generally less in magnitude than SCA variances at both locations, revealing that a large part of total variability for tasseling inheritance was under non-additive gene legacy.…”
Section: Days To Tasselingmentioning
confidence: 96%
See 2 more Smart Citations
“…Such results indicate that the location affects the non-additive gene actions more than additive genetic effects in tasseling. However, Aly and Mousa (2011) and Zoric et al (2022) have reported significant GCA and SCA variances for most characters including tasseling in maize, emphasizing the function of both additive and non-additive components. GCA variances for tasseling were generally less in magnitude than SCA variances at both locations, revealing that a large part of total variability for tasseling inheritance was under non-additive gene legacy.…”
Section: Days To Tasselingmentioning
confidence: 96%
“…Sweet corn (Zea mays L. var. 'saccharata') is a type of corn with a creamy texture and mutant endosperm, which contains about three to eight times more sugar than other types of corn (Chozin et al, 2017;Sheng et al, 2018;Zoric et al, 2022). Global production is relatively few grown on a small area of 1.06 million ha due to restricted research work, unexpected climatic changes, and tapered genetic makeup (Lertrat and Pulam, 2007;Fahad et al, 2022;Shojaei et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fourth article, the authors presented a method for effectively and accurately predicting the effect of environmental conditions on the grain yield of maize varieties belonging to different maturity groups [10]. The presented experiment concerned the analysis of several important environmental parameters in terms of the yield efficiency of three groups of corn varieties in VCU (value for cultivation and use) experiments in Croatia.…”
Section: Papers In This Special Issuementioning
confidence: 99%
“…Effectively, the BLUP presents a favorable characteristic for the shrinkage of the estimators towards the mean and reduces its variance and increases its predictive precision [35]. The REML/BLUP procedure has been widely used in annual allogamy breeding crops such as Zea mays (L.) [36][37][38] and autogamy such as Glycine max (L.) [39,40]. The procedure has also been applied to selection for perennial crops e.g., Prunus persica (L.) [41], but the approach is less common.…”
Section: Introductionmentioning
confidence: 99%